The CcpA regulon of Streptococcus suis reveals novel insights into the regulation of the streptococcal central carbon metabolism by binding of CcpA to two distinct binding motifs. Issue 1 (4th March 2014) - Willenborg, Jörg; de, Astrid; Jarek, Michael; Valentin‐Weigand, Peter; Goethe, Ralph
Summary S treptococcus suis (S. suis) is a neglected zoonotic streptococcus causing fatal diseases in humans and in pigs. The transcriptional regulator CcpA (catabolite control protein A) is involved in the metabolic adaptation to different carbohydrate sources and virulence of S. suis and other pathogenic streptococci. In this study, we determined the DNA binding characteristics of CcpA and identified the CcpA regulon during growth of S. suis. Electrophoretic mobility shift analyses showed promiscuous DNA binding of CcpA to cognate cre sites in vitro. In contrast, sequencing of immunoprecipitated chromatin revealed two specific consensus motifs, a pseudo‐palindromic cre motif (WWGAAARCGYTTTCWW) and a novel cre2 motif (TTTTYHWDHHWWTTTY), within the regulatory elements of the genes directly controlled by CcpA. Via these elements CcpA regulates expression of genes involved in carbohydrate uptake and conversion, and in addition in important metabolic pathways of the central carbon metabolism, like glycolysis, mixed‐acid fermentation, and the fragmentary TCA cycle. Furthermore, our analyses provide evidence that CcpA regulates the genes of the central carbon metabolism by binding either the pseudo‐palindromic cre motif or the cre2 motif in a HPr(Ser)∼P independent conformation.